2016
DOI: 10.1080/03007995.2016.1206872
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early goal directed therapy in the treatment of severe sepsis and/or septic shock

Abstract: EGDT significantly reduced mortality in patients with severe sepsis and/or septic shock over 15 years since its publication. Recent studies examining usual care with EGDT have similar mortality benefit because of the diminished treatment effect. This treatment effect is diminished for multiple reasons. With progress in the management of this disease the benefit of EGDT on overall mortality has become comparable with the usual care for sepsis patients. This is because many of the components of EGDT have been in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 47 publications
(76 reference statements)
0
18
0
1
Order By: Relevance
“…Therefore, this progress may be attributed to the new recommendation of EGDT, which may achieve aggressive correction of septic shock when combined with early appropriate antibiotic administration. Nonetheless, the mortality rate of patients with severe sepsis declined following the implementation of EGDT ( 84 87 ). A recent meta-analysis study also concluded that important factors contributing to improved outcome are time-to-first antibiotic administration and appropriate antibiotic use ( 88 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this progress may be attributed to the new recommendation of EGDT, which may achieve aggressive correction of septic shock when combined with early appropriate antibiotic administration. Nonetheless, the mortality rate of patients with severe sepsis declined following the implementation of EGDT ( 84 87 ). A recent meta-analysis study also concluded that important factors contributing to improved outcome are time-to-first antibiotic administration and appropriate antibiotic use ( 88 ).…”
Section: Discussionmentioning
confidence: 99%
“…Methods We retrospectively analyzed 11,499 32.2%, and 29.6%; p<0.001), 1-year mortality, (64.6%, 56.8%, 52.5%, and 46.7%; p<0.001), and in-hospital mortality (35.4%, 34.3%, 31.6%, and 29.9%; p=0.018). In addition, obese patients had notably longer mechanical ventilation periods and intensive care unit and hospital lengths of stay.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have considered the relationship between obesity, and short-and long-term prognosis of patients admitted to the intensive care unit (ICU) [9]. However, research on the relationship between obesity and short-term and long-term prognosis in patients with sepsis diagnosed by ICU based on large data samples is relatively limited [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…EGDT was found to significantly benefit mortality as compared with standard care in 5 of the 13 studies (3,15,17,27,35). Of these, four were performed in China and one was the Rivers seminal study.…”
Section: Main Findingsmentioning
confidence: 99%
“…Note that EGDT also implies extensive "bundled" treatments including immediate fluid resuscitation, early and adequate source control and/or initiation of antibiotics, and tailored use of vasopressors, inotropes and blood transfusion (39). Although study protocols dictated that the control group was not guided by ScvO 2 monitoring but directed by the treating physician, many components of the SSC bundle could have been introduced (35,40), which may explain why no significant difference was found between standard and EGDT-driven care. As an example, baseline ScvO 2 in these studies was higher than 70% in most of patients, which may reflect an aggressive medical therapy before randomization or the inclusion of less severe patients than in the Rivers study.…”
Section: Main Findingsmentioning
confidence: 99%